2015
DOI: 10.1016/j.jpor.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based bone regeneration for alveolar ridge augmentation – Cell source, endogenous cell recruitment and immunomodulatory function

Abstract: Alveolar ridge plays a pivotal role in supporting dental prosthesis particularly in edentulous and semi-dentulous patients. However the alveolar ridge undergoes atrophic change after tooth loss. The vertical and horizontal volume of the alveolar ridge restricts the design of dental prosthesis; thus, maintaining sufficient alveolar ridge volume is vital for successful oral rehabilitation. Recent progress in regenerative approaches has conferred marked benefits in prosthetic dentistry, enabling regeneration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 208 publications
2
15
2
Order By: Relevance
“…Furthermore, transgenic overexpression of P-glycoprotein or VEGF165 in BMSCs significantly increased stem cell-induced osteogenesis as well [19, 20]. In addition, SDF-1 was found to be closely associated with osteogenesis and angiogenesis [49, 50]. In the present study, we showed that SDF-1α overexpression in BMSCs significantly promoted bone regeneration by osteogenesis and angiogenesis.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, transgenic overexpression of P-glycoprotein or VEGF165 in BMSCs significantly increased stem cell-induced osteogenesis as well [19, 20]. In addition, SDF-1 was found to be closely associated with osteogenesis and angiogenesis [49, 50]. In the present study, we showed that SDF-1α overexpression in BMSCs significantly promoted bone regeneration by osteogenesis and angiogenesis.…”
Section: Discussionsupporting
confidence: 50%
“…In the case of soft tissue, zirconia needles are able to accelerate stem cell recruitment when compared to stainless steel needles 6. Stem cell recruitment is an important factor for new bone formation 14. We were unable to clearly identify the possibility of unknown zirconia effects with the present results.…”
Section: Discussioncontrasting
confidence: 62%
“…Therefore, new types of bone grafts created with cultured autologous cells have recently been reported. In particular, bone marrow mesenchymal stem cells and adipose tissue have received attention, with successful bone tissue engineering with those cell types reported [7073]. The present results demonstrated that NCDFCs possess the capability of osteoblastic differentiation following stimulation with BMP-2, indicating their potential use as a cell source for bone tissue engineering.…”
Section: Discussionsupporting
confidence: 59%